The Regional Western Sweden SOM Survey 2015 - SOM Institute, University of Gothenburg (University of Gothenburg, 2017)
Western SOM has been conducted yearly since 1992, but was initially limited to residents of Gothenburg and its surrounding municipalities. In 1998, the survey was extended to include the entire Västra Götaland County plus the municipality of Kungsbacka.

The purpose of the regional surveys is to enable SOM researchers to study attitudes and behaviour linked to local and regional issues. They emphasise public services and media, although many of the questions are identical with those used in National SOM in order to make the answers comparable both between the regions and with Sweden at large.

Purpose:

Study attitudes and behaviours that are linked to local and regional issues and phenomena.

Väst-SOM har genomförts varje höst sedan 1992. Fram till 1997 omfattade studien Göteborg med kranskommuner, Undersökningen utökades sedan till att omfatta hela Västra Götalands län samt Kungsbacka kommun. Flertalet frågor har ställts i många år och svaren bidrar till att bibehålla tidsserier som sträcker sig från undersökningens början 1992. Frågorna fokuserar speciellt på områden som är aktuella på regional nivå så som offentlig service och trafikvanor. I 2015 års undersökning ingick ett antal frågor om konsumtion och miljö. Många av frågorna är identiska med frågor i Riks-SOM och Syd-SOM. Dessa studier är därmed jämförbara med varandra, både mellan de bägge regionerna och med Sverige som helhet.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser.
Den västsvenska SOM-undersökningen 2015
Väst-SOM 2015
Keywords: housing; boende; occupations; yrken; public sector; offentlig sektor; environment; miljö; environmental degradation; miljöförstörelse; trust; förtroende; european union; europeiska unionen; political interest; politiskt intresse; local government services; kommunal service; public transport; kollektivtrafik; medical care; sjukvård; public services; offentlig service; news; nyheter; privatization; privatisering; income; inkomst; political participation; politiskt deltagande; sick leave; sjukfrånvaro; religious practice; religionsutövning; democracy; demokrati; internal politics; inrikespolitik; political parties; politiska partier; internet use; internetanvändning; dental care; tandvård; politicians; politiker; local government organizations; kommunala organisationer; social participation; socialt deltagande; working conditions; arbetsförhållanden; households; hushåll; local community facilities; lokala serviceinrättningar; clubs; föreningar; leisure time activities; fritidsaktiviteter; educational levels; utbildningsnivå; traffic; trafik; political attitudes; politiska åsikter; state health services; statlig hälso- och sjukvård; social networks; socialt nätverk; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap